Introduction: A brief journey through the 80 year history of the International Association of Schools of Social Work - Lynne M. Healy (Social Work and Society)
The leaders of the International Association of Schools of Social Work (IASSW) have played major roles in shaping the organization over its 80 year history. This brief introduction will put their roles in the context of the organization's history. While influenced by its presidents in significant ways, the organization's trajectory has also been affected by the political, economic and social developments of the 20th century and the beginning of the 21st. Significant changes have occurred in the organization and in social work education, yet, as Feustel (2006) observed,"the history of the IASSW demonstrates lines of continuity that are even more remarkable for the fact that it was caught up in the great historical ruptures of the 20th century" (p. 3).